Mechanical and microstructure analysis of AA6061 and Ti6AI4V fiber laser butt weld - Casalino, Giuseppe; D'Ostuni, Sonia; Guglielmi, Pasquale; Leo, Paola; Mortello, Michelangelo; Palumbo, Gianfranco; Piccininni, Antonio (Elsevier, 2017)
Dissimilar metal welding involves the joining of two or more different pure metals or alloys, usually by melting and mixing and often with the addition of filler metal. There are several types of dissimilar metal welds including stainless steel, either as base metal or as filler metals. Dissimilar metal joints have distinctive features because of differences in the chemical composition of base metal and filler material. Their alloying elements will diffuse intensely during welding. The structures near the fusion line are very complex. Despite of great potentiality in aircraft and automotive industries, dissimilar joining of hybrid Al-Ti structures is often challenging because of the unavoidable formation of brittle intermetallic compounds, mixing of molten phases, and significant differences in material properties. In this work, dissimilar 2 mm thickness AA6000 and Ti6Al4V butt joints were produced by shifting an Yb fiber laser beam on the upper surface of the Ti sheet. Neither filler wire nor groove preparation was adopted. Different working conditions and seam shapes were assessed. The welds were characterized in terms of metallurgical and mechanical behaviors.
Keywords: Fiber laser welding; Dissimilar weld; Mechanical and microstructure properties